Immunogenicity of therapeutic peptide products: bridging the gaps regarding the role of product-related risk factors - Puig, Montserrat; Shubow, Sophie (Frontiers in Immunology, 2025)
The global market for therapeutic peptides is projected to continue to grow at a fast pace in the coming years in response to high demand for these products. The increasing complexity of chemical and recombinant peptide manufacturing processes may impact product quality attributes, including as related to immunogenicity risk. While it is well established that product-related factors, including impurities, can impact the immunogenicity of a biologic product, assessing the actual impact of a specific product quality attribute on immunogenicity is difficult. Despite significant advances in the analytical characterization of complex peptide products, gaps still exist in our understanding of the significance of impurities to the overall peptide immunogenicity risk, and questions remain about what the best-suited control strategies are. These gaps have the largest impact on the assessment of immunogenicity risk of follow-on therapeutic peptide products, when clinical data are not available to inform that risk. Current regulatory guidance on impurity qualification thresholds is sparse, and in vitro and in silico immunogenicity assessment methods for evaluating the immunogenicity risk of impurities present technical and methodological limitations. We highlight these challenges and offer points to consider for handling them.